Old Armenian Layer of Modern Armenian Reciprocal Verbs - ZAKYAN, HRANUSH (Bulletin of Yerevan University B: Philology, 2021)
Old Armenian layer of modern Armenian reciprocal verbs includes approximately 150 verbs (about 30% of 500 verbs of the Old Armenian). About 50 reciprocal verbs passed into modern Armenian without any semantic and structural changes, and about 100 of them underwent certain changes. Modifications in orthography and word formation of reciprocal verbs (structural modifications) have systemic character and are not related to the reciprocal voice. Semantic changes appear with widening, narrowing, and modifying the volume of the verbs, which have retained the reciprocal voice.